Analisis Dampak Keterbukaan Perdagangan Internasional Terhadap Ketimpangan Pendapatan dalam Perspektif Ekonomi Islam pada 34 Provinsi di Indonesia Tahun 2018-2022 - Lisa Anggraini; Yetri Martika Sari; Nurlaili Nurlaili; Ghina Ulfah Saefurrahman; Alief Rakhman setyanto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to analyze the impact of international trade openness on income inequality. The impact of international trade openness is to increase foreign direct investment entering a country. The higher the level of foreign direct investment (FDI), the greater the possibility of income inequality. This can be caused by the uneven trickling down effect of foreign investment. High unemployment rates can result in lower incomes for the remaining workers, which in turn increases income inequality. Then, high inflation can cause a decrease in people's purchasing power, which in turn can increase income inequality. The research method used is a quantitative method. The type of data used is secondary data taken from the official website of the Indonesian Central Statistics Agency (BPS). The data analysis method used in this research is panel data analysis, regression model selection, classical assumption testing, and hypothesis testing using a data analysis tool, namely E-views version 10. The results of this research show that Foreign Direct Investment (FDI) has a positive effect and significant to income inequality, the Open Unemployment Rate (TPT) has no effect on income inequality, and Inflation has a negative and significant effect on income inequality